Semi-3D transient simulation of a nanofluid-base photovoltaic thermal system integrated with a thermoelectric generator - Kolahan, Arman; Maadi, Seyed Reza; Kazemian, Arash; Schenone, Corrado; Ma, Tao (Energy conversion and management, 2020)
[Display omitted] •A semi-3D transient code is developed to study feasibility of PVT-TEG system.•The performance of PVT-TEG and PVT system are studied comparatively during the day.•The effects of different parameters on the performance of systems are studied.•The energy proportion of each part in the systems is expressed. Thermoelectric generators (TEGs) can produce electricity from the temperature gradients. A combination of TEG with photovoltaic thermal (PVT) systems can be a possible solution for the improvement of their electrical performance. To evaluate the feasibility of using TEG in PVT systems, a comparison between only the PVT system and PVT system integrated with TEG (PVT-TEG) is conducted using numerical simulation. A semi-transient numerical code is developed by FORTRAN software to simulate both PVT and PVT-TEG systems. The governing equations are solved by Tridiagonal Matrix Algorithm (TDMA) using an implicit formulation discretizing by a center-differencing scheme. In this study, aluminum-oxide/water (Al2O3/water) nanofluid is selected as working fluid due to the performance improvement of the systems. Both energy and exergy analysis are conducted to estimate the performance of the nanofluid based PVT-TEG system. The results indicate that the PV unit in both PVT and PVT-TEG systems can generate nearly the same electrical power. However, the PVT-TEG system has 2.5%–4% higher overall electrical energy efficiency compared to only the PVT system. It has been found, in all considered parameters, the PVT-TEG system compared to the PVT system in terms of overall exergy efficiency shows a better performance, while in terms of overall energy efficiency shows poor performance. Furthermore, according to the parametric analysis, there is a direct relation between inlet temperature and photovoltaic (PV) plate temperature, whereas there is an indirect correlation between the inlet temperature and TEG sides difference temperatures.